Effect of Lactobacillus plantarum and Staphylococcus xylosus on flavour development and bacterial communities in Chinese dry fermented sausages. (September 2020) - Xiao, Yaqing; Liu, Yingnan; Chen, Conggui; Xie, Tingting; Li, Peijun
Graphical abstract: Highlights: Bacterial diversity of dry sausages was analysed by high-throughput sequencing. L. plantarum and S. xylosus promoted the proteolysis and lipolysis in the sausages. The inoculation with mixed strains improved the flavour of the sausages. Growth of unwanted bacteria was inhibited in the inoculated sausages. Flavour development was attributed to the improved microbiological quality. Abstract: The use of starter cultures helps to improve the quality and safety of traditional meat products. In this study, the effects of Lactobacillus plantarum R2 and Staphylococcus xylosus A2 inoculation on microbial community, lipolysis, proteolysis, and volatile compounds in Chinese dry fermented sausages were investigated. Culture-dependent and culture-independent high-throughput sequencing) methods were employed to evaluate the bacterial communities. Results showed that the total contents of free fatty acids (FFAs) and free amino acids (FAAs) were increased by inoculating the starter cultures, especially a mixed culture. A significant decrease in pH and water activity was observed in the inoculated sausages ( p  < 0.05). Moreover, the inoculation treatment enhanced the competitiveness of dominant bacteria and inhibited the growth of unwanted bacteria. This was beneficial to promote the release of FFAs and FAAs and to prevent the formation of off-flavours and rancidity. Thus, the flavour development in the inoculated dry fermented sausages was attributed to the improvements in microbiological quality.